Faith and slavery in the Presbyterian diaspora - Taylor, William Harrison, 1980- (Studies in eighteenth-century America and the Atlantic world., 2016)
Faith and Slavery considers how in diverse places-the New Hebrides, Scotland, the United States, and East Central Africa-the Presbyterian faith shaped men's and women's interpretations of and interactions with chattel slavery. The chapters highlight how the particular ways Presbyterians framed the Reformed Tradition made slavery an especially problematic and fraught issue for adherents to the faith, and led to a variety of reactions to slavery-ranging from abolitionism, to indifference, to support.